Integrated Thematic Learning Program For Teachers Of SD Muhammadiyah In The City Of Medan - Akrim Akrim; Nurzannah Nurzannah; Nurman Ginting (Proceeding International Seminar of Islamic Studies, 2019)
The purpose of this community service is; firstly to fulfill one of the tri dharma requirements of tertiary institutions, secondly to improve the skills of Muhammadiyah elementary school teachers in Medan in developing Integrated Thematic Learning programs and being able to implement them in real class learning. The method used in achieving these objectives is to conduct counseling and training in the form of Workshops and Peer Teaching, as well as mentoring in creating integrated thematic learning programs to the monitoring and evaluation in implementing them in class. The specific target of community service is for Muhammadiyah elementary school teachers in the city of Medan to design, implement and evaluate the Integrated Thematic learning program that they carry out, which in the end the learning process can be carried out effectively and efficiently.